Producing xylan/Eudragit (R) S100-based microparticles by chemical and physico-mechanical approaches as carriers for 5-aminosalicylic acid - Silva, Acarilia Eduardo; Oliveira, Elquio Eleamen; Salgado Gomes, Monique C.; Marcelino, Henrique Rodrigues; Holanda Silva, Karen C.; Souza, Bartolomeu Santos; Nagashima-, Toshiyuki; Ayala, Alejandro Pedro; Oliveira, Anselmo Gomes de [UNESP]; Tabosa do Egito, Eryvaldo Socrates (Informa Healthcare, 2013)
Xylan is a biopolymer found in a variety of cell wall plants. Eudragit (R) S-100 (ES100), a pH-dependent polymer, is used as a coating material in gastroresistant delivery systems. In this study, microparticles based on both polymers were produced by interfacial cross-linking polymerisation and/or spray-drying technique in order to investigate feasibility and stability of the systems. Size and morphology of the microparticles were characterised by optical and SEM while FT-IR, thermal analysis (TG/DTA), and X-ray diffraction (XRD) evaluated the drug-polymer interactions and the thermal behaviour of the systems. FT-IR confirmed the absence of chemical interaction between the polymers. TG/DTA analysis showed a higher stability for spray-dried microparticles and XRD data proved the amorphous feature of both carriers. The results reveal that xylan/ES100 microparticles can be produced by chemical or physico-mechanical ways, the latter being the best option due to the lack of toxic cross-linking agents and easy scale-up.
Keywords: Cross-linking; infrared spectroscopy; polymer-biopolymer interaction; spray-drying; thermal analysis